The legislative branch : making laws - Duignan, Brian; DeCarlo, Carolyn (Checks and balances in the U.S. government., 2019)
Examines the legislative branch of the U.S. government in the federal system of checks and balances, and discusses its creation, powers and functions, and the benefits and drawbacks of major legislation that it has passed in the modern era. Includes color photographs, a glossary, and further resources.